QUANTIFYING THE IMPACT OF RUNNING CADENCE ON BIOMECHANICS, PERFORMANCE, AND INJURY RISK: A PHYSICS-BASED ANALYSIS - Mohammed Ameen, Rayan B. (Science Journal of University of Zakho, 2024)
Running cadence is crucial in running biomechanics and physiology, impacting performance and injury risk. The relationship between running cadence, height, weight, and gender is explored using data from 29 participants (14 males, 15 females) with varying attributes. Taller individuals tend to have a lower cadence due to longer stride length, while fewer steps are required by heavier individuals at the same pace. A higher cadence is observed in males, possibly due to differences in leg length and muscle fiber composition, although considerable variability exists among individuals of both genders. Linear regression analysis revealed robust models for both genders, with negative correlations between cadence and height, indicating that increased cadence correlates with decreased height for males and females. Females typically have higher BMI than males, with BMI variability in the population. Weight influences running cadence by affecting ground force. Heavier individuals may take fewer steps, but risk increased strain on joints and muscles, raising injury risk. Furthermore, the connection between running cadence and injury risk is investigated. It is found that adjusting cadence significantly reduces stress on weight-bearing joints and prevents common overuse running injuries. It is demonstrated by several reputable studies in the field that even minor cadence increases greatly reduce stress on knee and hip joints during running, making it a commendable method for injury prevention. In conclusion, while height and weight impact running cadence, each person’s cadence is unique and influenced by various factors beyond gender alone. Understanding the relationship between running cadence and its impact on injury prevention is crucial for runners seeking to improve performance and avoid injuries.